Contribuições dos registros de representação semiótica para a compreensão dos números decimais : um estudo com alunos do 6 º ano - Brita, Flávia Cheroni da Silva (2015)
The objective of this study is to favour the learning of Decimal Numbers by sixth grade students, with theoretical backing on Raymond Duval's Registers of Semiotic Representation. The referred author considers that the access to the mathematical object is given by the coordination of at least two registers, stating the necessity of conventions in teaching and learning situations. Such theoretical support has subsidized the elaboration of an activity sequence which contributed for the students to get to the conversions related to the registers of semiotic representations of the Decimal Numbers, such as decimal numeric, numeric fractions, numeric in the form of percentage, monetary numeric, discrete data and continuous data. This sequence was carried out with a group of twenty students in the sixth grade from a public state school in Parana, who met with the researcher once a week,during six weeks as an extra-school activity. The meetings were recorded in audio and video. The Educational Engineering conducted the research methodologically, guiding the implementation and investigation in the class room, relating the theory, the students and the mathematical knowledge of Decimal Numbers. The analysis occurred by means of the registers written by the students, as well as the transcription of their sayings. The analysis points out that the sequence of activities in light of the registers of semiotic representations favoured the students in relation to familiarity with the registers, stimulated transformations and subsidized them in making conversions, being able to comprehend the Decimal Numbers.